Podocarpus latifolius (Thunb.) R.Br. ex Mirb. Extracts Inhibit the Growth Some Bacterial Triggers of Rheumatoid Arthritis and Ankylosing Spondylitis - Mpala, Lindiwe Nomathemba; Chikowe, Getmore Rumbudzai; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Podocarpus latifolius (Thunb.) R.Br. ex Mirb. is a large tree that is native to southern Africa. This species has been used extensively for multiple therapeutic purposes across the southern part of the African continent. Despite this, P. latifolius leaf extracts have not been rigorously examined growth inhibitory properties against many bacteria, including the bacterial triggers of autoimmune inflammatory diseases. Materials and Methods: The antimicrobial activity of P. latifolia leaf solvent extractions was investigated by disc diffusion and growth time course assays against some bacterial triggers of rheumatoid arthritis and ankylosing spondylitis. The growth inhibitory activity was further quantified by MIC determination. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Methanolic and aqueous P. latifolia leaf extracts were good inhibitors of P. mirabilis and K. pneumoniae. The inhibitory activity of both extracts was particularly noteworthy against the bacterial trigger of ankylosing spondylitis (K. pneumonia), with MICs of 343 and 557 μg/mL determined for the methanolic and aqueous extracts respectively. The extracts also displayed noteworthy activity against a bacterial trigger of rheumatoid arthritis (P. mirabilis), with MICs of 580 and 634 μg/mL respectively. The antibacterial activity of the methanolic and aqueous P. latifolia leaf extracts were further investigated by growth time course assays, which showed significant growth inhibition in cultures of P. mirabilis and K. pneumoniae within 1 hr of exposure. The extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indicating their safety for prophylactic use in preventing these autoimmune inflammatory diseases. Conclusion: The lack of toxicity of the P. latifolia leaf extracts and their growth inhibitory bioactivity against the bacterial triggers of rheumatoid arthritis and ankylosing spondylitis indicate their potential in the development of new therapies targeting the onset of these diseases.
Keywords: Podocarpaceae; Yellowwood; South African plants; Rheumatoid arthritis; Ankylosing spondylitis; Antibacterial activity; Medicinal plants.